Donor DBH excitons and magnetism of Mn doped ZnO. (November 2019) - Sokolov, V I; Gruzdev, N B; Vazhenin, V A; Fokin, A V; Korolev, A V; Menshenin, V V; Surikov, V T; Yemelchenko, G A
Abstract: In this paper the results of the study of optical absorption, photo-EPR signals and magnetic measurements of hydrothermal single crystals of zinc oxide doped with manganese were presented. Several lines were detected in optical absorption spectra at the temperature of 4.2 K and 77.3 K for σ- and π- polarizations of light in a 1.72–2.3 eV spectral range. These lines are attributed to a donor exciton [(d 5 + h)e] that emerges as a result of the Coulomb binding of a free s electron and a hole, which is localized on p–d hybridized states. Properties of these lines are significantly different from the properties of lines of donor and acceptor excitons in II-VI:3d compounds. In EPR-spectra of Zn1- x Mn x O crystals the intensity of allowed and forbidden EPR-signals of Mn 2+ ( d 5 )-ions does not change under the illumination while the intensity of EPR-signals of unintentional Fe 3+ ( d 5 )-ions decreases by 70 %. The value of the magnetic susceptibility of Zn1- x Mn x O ( x = 0.0009) is in linear dependence with temperature, which agrees with the Curie equation. Temperature dependence of the inverse value of the Mn 2+ magnetic susceptibility indicates that the exchange interaction in ZnO:Mn crystals is absent. New experimental results allow us to assume that investigated Zn1- x Mn x O ( x = 0.0009) samples are semiconductors in the forbidden gap of which the donor level of d 5 /d 4 does not exist. The hybridization of d 5 states of Mn 2+ and p states of the nearest four oxygen ions O 2- leads to pushing out the antibonding DBH-states ( d 5 + p ) into the forbidden gap. The transitions of electrons from DBH-states to the conduction band provide a broad band of the impurity absorption in ZnO:Mn. Below this band we observed a, b, c and d lines, which are called dbh-donor excitons [(d 5 +h)e].